Climatic Influence on Growth Performance of Abies spectabilis in the Himalayas - Pandey, Krishna Prasad; Wellstein, Camilla; Bräuning, Achim; Bhuju, Dinesh Raj (Forests, 2025)
Climate change has affected forest ecosystems across the world over the past century. However, its impact is particularly high in the Himalayas due to increasing temperatures, extreme precipitation events, and regional droughts. In this context, a review of the current stage of research was deemed necessary to understand the adaptation of a key conifer species to climate variability in the Central Himalayas. Hence, we conducted a systematic review of published peer-reviewed journal articles addressing the growth performance of Abies spectabilis (D. Don) Spach in the Central Himalayas. From this review, three main patterns of climate response have emerged: a positive correlation of radial tree growth with temperature of the current and previous growing seasons, tree growth limitation by winter temperature, and by temperature or moisture in the pre-monsoon season. Overall, results indicate an elevation-dependent temperature sensitivity, a crucial role of moisture availability, and seasonal shifts in climate–growth relationships, reflecting the species’ adaptability to changing climate conditions. Our review revealed that studies on elevation-dependent adaptation of wood anatomical traits by A. spectabilis are still rare. The tree-ring growth of this species shows a complex response to climate variability, with increasing as well as decreasing growth trends across its distribution range.
CRIS-Team Scopus Importer:2025-04-04
Keywords: Abies spectabilis; climatic variability; dendrochronology; Himalaya; quantitative wood anatomy